Indonesian Sharia Bank KUR Innovation Through A Digital Platform - Kartika Marella Vanni; Tria Noviani (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
The ease of transactions at financial institutions has now been facilitated by the existence of technology that is updated on an ongoing basis. This is also what makes Islamic banking innovate on its products, one of which makes people's business credit (KUR) sharia accessible through a digital platform in collaboration with the telecommunications service company "Telkomsel". This easy access to Sharia KUR financing can be accessed through platforms available on your cellphone under the name DigiPOS and 99%Usahaku. With this innovation, it is hoped that business actors can increase their capacity to go digital so they can compete with established businesses. The existence of this phenomenon, the author will discuss about how the mechanism of KUR Syariah and implementation of digital-based KUR Syariah. The research method that the author uses is descriptive qualitative research using field research. The data source used is primary data collected using direct interview techniques with Indonesian Islamic Banks. And secondary data were taken from various literatures related to research.